2012
DOI: 10.1002/j.0022-0337.2012.76.6.tb05310.x
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Mineral Trioxide Aggregate in Endodontics Education in Dental Schools in Turkey

Abstract: The aim of this study was to assess the current status of mineral trioxide aggregate (MTA) as an educational material in dental schools in Turkey. A survey was sent to senior members of the endodontic departments of seventeen dental schools; fourteen responded. All respondents reported that they used MTA in their clinical practice, with apexiication, perforations, retrograde illings, and root resorptions being the most frequently occurring treatment procedures. All reported that information was given to studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Although much literature from the UK, Europe and the USA describes the high cost of MTA as being the main barrier to its widespread clinical use , the results of this study show that in the Australian context, the main factor which restricts the use of MTA is a lack of formal training in how to use the material appropriately. It is noteworthy that the majority of GD members of the ASE expressed a need to undertake hands‐on training in the use of MTA.…”
Section: Discussionmentioning
confidence: 74%
“…Although much literature from the UK, Europe and the USA describes the high cost of MTA as being the main barrier to its widespread clinical use , the results of this study show that in the Australian context, the main factor which restricts the use of MTA is a lack of formal training in how to use the material appropriately. It is noteworthy that the majority of GD members of the ASE expressed a need to undertake hands‐on training in the use of MTA.…”
Section: Discussionmentioning
confidence: 74%
“…, Kahler & Rossi‐Fedele ) and difficult handling characteristics have emerged as potential drawbacks (Parirokh & Torabinejad , von Arx , Tanalp et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…However, long setting time, tooth discoloration, high cost (Tanalp et al . , Foley , Walker et al . , Kahler & Rossi‐Fedele ) and difficult handling characteristics have emerged as potential drawbacks (Parirokh & Torabinejad , von Arx , Tanalp et al .…”
Section: Introductionmentioning
confidence: 99%
“…33 However, MTA is not without potential drawbacks, including a long setting time, tooth discoloration, high cost and difficult handling characteristics. 23,27,28,34,35 With continued attempts to develop a material without the drawbacks of MTA, MTA-like cements have emerged with descriptors such as "bioceramics" 36 and "bioactive endodontic cements." 23 A review of properties of MTA and MTA-like cements by Ha et al 37 indicated that despite the differences in terminology, these cements are similar in their elemental compositions to MTA and, hence, fall within the description of MTA.…”
Section: Introductionmentioning
confidence: 99%
“…However, MTA is not without potential drawbacks, including a long setting time, tooth discoloration, high cost and difficult handling characteristics. 23,27,28,34,35…”
Section: Introductionmentioning
confidence: 99%